Spatial and temporal comparisons of double-crested cormorant diets following the establishment of alewife in Lake Champlain, USA - DeBruyne, Robin L.; DeVault, Travis L.; Duerr, Adam E.; Capen, David E.; Pogmore, Fred E.; Jackson, James R.; Rudstam, Lars G. (DigitalCommons@University of Nebraska - Lincoln, 2012)
Increasing numbers of double-crested cormorants (Phalacrocorax auritus) on Lake Champlain have caused concerns related to potential impacts on the yellow perch (Perca flavescens) population. However, with the establishment of alewife (Alosa pseudoharengus) in 2003, cormorant foraging may have changed. We examined cormorant diets from four areas of Lake Champlain to assess past, current, and potential future impacts of cormorants on the changing fish community. During the breeding seasons of 2001–2002 and 2008–2009, we observed spatial and temporal differences in cormorant diets. Yellow perch dominated diet composition during 2001–2002 at Young Island (73% and 90% yearly weight totals) during all reproductive periods. Four Brothers Islands diet composition in 2002 varied according to reproductive period. In 2008 and 2009, alewife were predominant in diets at Four Brothers Islands (56% and 71%) and the South site (65% and 62%), with yellow perch comprising a high proportion of diets at Young Island (44% and 56%). Results from a MANOVA confirmed differences among sites, reproductive period, and the interaction of these factors (P < 0.0001) when describing diet compositions for the post-alewife years. PCA results denoted a general shift in cormorant diets from 2001–2002 to 2008–2009. Our study demonstrated that the diet of piscivorous birds may shift with a new forage species and may vary significantly within a single large water body. Accordingly, efforts to manage piscivorous birds with the intent to decrease mortality of specific fish species should be site specific when possible.